Organization of Mother and Infant Care Services (Urban) in Indonesia - R. Sutedjo (Indonesian Pediatric Society, 1974)
In Jakarta, being the capital of Indo-nesia, mother and infant care startedin the hospitals long before the se-cond world war, mainly in the cura-tive sense.